1995
DOI: 10.1161/01.cir.92.7.1758
|View full text |Cite
|
Sign up to set email alerts
|

Kuopio Atherosclerosis Prevention Study (KAPS)

Abstract: These data establish the antiatherogenic effect of LDL-C lowering by pravastatin in hypercholesterolemic men in a primary prevention setting and suggest a greater effect in smokers than in nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(128 citation statements)
references
References 26 publications
3
118
0
7
Order By: Relevance
“…Clinical trials have frequently used change in IMT over time (i.e. IMT progression rate) as a surrogate variable for vascular risk [2][3][4][5]. However, it has become increasingly evident that the risk of an atherosclerotic plaque to rupture and to give rise to an acute clinical event is not only dependent on plaque size but more on the composition of the plaque.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have frequently used change in IMT over time (i.e. IMT progression rate) as a surrogate variable for vascular risk [2][3][4][5]. However, it has become increasingly evident that the risk of an atherosclerotic plaque to rupture and to give rise to an acute clinical event is not only dependent on plaque size but more on the composition of the plaque.…”
Section: Introductionmentioning
confidence: 99%
“…Sample size estimation was based on similar assumptions as for the study on carotid atherosclerosis progression [7]: with reference to what had been demonstrated in another primary prevention trial, the annual atherosclerotic progression rate of IMT was estimated to be 0.049 0.04 mm in untreated women [17]. HRT was estimated to result in a 50% slowing of progression.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of myo pathy during monotherapy with statins is approxi mately 1 in 1000, although the combination with fibrates, cyclosporin, nicotinic acid and erythromycin might amplify this risk [54], In animal studies, treatment with HMG-CoA re ductase inhibitors has been shown to retard the de velopment of atherosclerosis [55,56]. Moreover, in tensive lipid lowering using HMG-CoA reductase inhibitors is the most effective in terms of inducing plaque regression and reducing the number of clini cal events in men with established CAD and PVD [18,19,25,28,[30][31][32][33][34][35][36][37][38][39][40][41]. Recently, a meta-analysis that pooled data from four studies treating men and women with 10-40 mg per day pravastatin for 2-3 years showed that a decrease in LDL-cholesterol of 28% from baseline was associated with a 62% reduc tion in the combined incidence of non-fatal and fatal myocardial infarction [57].…”
Section: L Hmg-coa Reductase Inhibitorsmentioning
confidence: 99%
“…Most of these tiñáis have shown slowing or arrest of progression of coronary atherosclerosis. Reports concerning femoral atherosclerosis are more scarce [7,[14][15][16]21,24,25], In several recent clinical trials on plasma lipid regu lation, measurements of carotid artery intima-media thickness (IMT) have been included, because coro nary and carotid atherosclerosis share coronary events as their major cause of morbidity and mortality [38][39][40][41]. Indeed, most of these studies have also shown a slowing of progression of IMT during lipid-lowering treatment.…”
Section: Introductionmentioning
confidence: 99%